A simple reducing water content technique for stingless bee honey (Heterotrigona itama) in South Kalimantan. Issue 1 (September 2020) - Halwany, W; Hakim, S S; Rahmanto, B; Wahyuningtyas, R S; Siswadi,; Andriani, S; Lestari, F
Abstract: Water content is one of the parameters of the honey product quality. Unlike Apis honey product, honey from stingless bee ( Heterotrigona itama ) have higher water content. To meet the required standard, reducing water content of stingless bee honey need to be done. Therefore, in this study we aim to find out the effect of using honey water content reducer device to water content and quality of stingless bee honey. We modified simple drying cupboard with heat pad to reduce honey water content. Moreover, nutrient analysis was carried out to know whether the drying process affect its nutrient quality. Six sample of stingless bee honey which was placed in a container (thickness=0.5 cm) and the temperature was set at 40°C. According to the study, to reach the recommended honey water content (21-22%) it takes approximately 3 hours with a value of R=0.848 in addition, drying treatment (40°C) did not affect the nutritional quality of stingless bee honey.